Polyaniline/Platinum Composite Cathode Catalysts Towards Durable Polymer Electrolyte Membrane Fuel Cells. Issue 11 (5th November 2020) - Kocher, K.; Hacker, V.
Abstract: Polymer stabilization proved to be a promising approach to increase the catalytic performance of common platinum/carbon based cathode catalysts (Pt/C) used in polymer electrolyte membrane fuel cells (PEMFCs). Platinum and polyaniline composite catalysts (Pt/C/PANI) were prepared by combining chemical polymerization reactions with anion exchange reactions. Electrochemical ex‐situ characterizations of the decorated Pt/C/PANI catalysts show high catalytic activity toward the oxygen reduction reaction (ORR) and, more importantly, a significant enhanced durability compared to the undecorated Pt/C catalyst. Transmission electron microscopy (TEM) investigations reveal structural benefits of Pt/C/PANI for ORR catalysis. All studies confirm high potential of Pt/C/PANI for practical fuel cell application. Abstract : Polyaniline/platinum composite cathode catalysts (Pt/C/PANI) represent highly efficient and durable electrocatalysts being vital in advancing fuel cell technology. A two‐step synthesis enables selective catalyst design so that, due to unique intermolecular interactions, the catalytic activity of an appropriate Pt/C/PANI catalyst doubled and its durability is three times higher compared to the Pt/C reference catalyst.